HIGHER ORDER THINKING SKILLS ASSESSMENT BASED ON ENVIRONMENTAL PROBLEM (HOTS-AEP): MENDESAIN EVALUASI PEMBELAJARAN ABAD 21 - Ilmi Zajuli Ichsan; Risky Hasanah; Syarifah Aini; Rizhal Hendi Ristanto; Mieke Miarsyah (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2019)
The ability of Higher Order Thinking Skills (HOTS) is one of the important aspects to solve environmental problems, in this case related to 21st century learning. The purpose of this study is to develop Higher Order Thinking Skills Assessment based on Environmental Problems (HOTS-AEP) in elementary school level. The research method used is research and development model Borg and Gall. The study was conducted in March-April 2019 at State Elementary School of Jatimulya 02, Tambun Selatan, Bekasi, West Java, Indonesia. The results show that HOTS-AEP is suitable for use in learning evaluation because it has a valid category according to experts with an average validation score of 3.63 and valid based on Pearson product moment calculations and has moderate reliability. This is because HOTS-AEP is very compatible with the context of problem-based environmental learning. The conclusion of this study is that HOTS-AEP is worthy of being used as an evaluation of learning for students at the elementary school level.